A Case of Beta-propeller Protein-associated Neurodegeneration due to a Heterozygous Deletion of WDR45. (8th August 2017) - Hermann, Andreas; Kitzler, Hagen H.; Pollack, Tobias; Biskup, Saskia; Krüger, Stefanie; Funke, Claudia; Terrile, Caterina; Haack, Tobias B.
Background: Static encephalopathy of childhood with neurodegeneration in adulthood is a phenotypically distinctive, X-linked dominant subtype of neurodegeneration with brain iron accumulation (NBIA). WDR45 mutations were recently identified as causal. WDR45 encodes a beta-propeller scaffold protein with a putative role in autophagy, and the disease has been renamed beta-propeller protein-associated neurodegeneration (BPAN). Case Report: Here we describe a female patient suffering from a classical BPAN phenotype due to a novel heterozygous deletion of WDR45 . An initial gene panel and Sanger sequencing approach failed to uncover the molecular defect. Based on the typical clinical and neuroimaging phenotype, quantitative polymerase chain reaction of the WDR45 coding regions was undertaken, and this showed a reduction of the gene dosage by 50% compared with controls. Discussion: An extended search for deletions should be performed in apparently WDR45- negative cases presenting with features of NBIA and should also be considered in young patients with predominant intellectual disabilities and hypertonia/parkinsonism/dystonia.